Market integration and structural transformation in a poor rural economy - Söderbom, Måns (Policy research working paper, 2009)
"By developing a simple theoretical model of the impact of market integration on sectoral output and employment in a poor rural setting, this paper demonstrates that trade can induce asymmetric growth. Under certain, plausible, assumptions, the non-farm sector will grow much faster than the agricultural sector when markets become integrated. Promoting market integration may thus be an effective way of encouraging diversification beyond agriculture and catalysing structural change in poor rural economies. "--World Bank web site